Longitudinal bidirectional relations between children’s negative affectivity and maternal emotion expressivity - Tan, Lin; Smith, Cynthia L. (Frontiers in Psychology, 2022)
Although children’s negative affectivity is a temperamental characteristic that is biologically based, it is framed within and shaped by their emotional environments which are partly created by maternal emotion expressivity in the family. Children, in turn, play a role in shaping their family emotional context, which could lead to changes in mothers’ emotion expressivity in the family. However, these theorized longitudinal bidirectional relations between child negative affectivity and maternal positive and negative expressivity have not been studied from toddlerhood to early school-age. The current study utilized a cross-lagged panel model to examine the reciprocal relations between children’s negative affectivity and maternal expressivity within the family over the course of early childhood. Participants were 140 mother-child dyads (72 boys, mean age = 2.67 years, primarily White). Mothers reported the positive and negative expressivity in the family and children’s negative affectivity in toddlerhood (T1), preschool (T2), and school-age (T3). Maternal negative expressivity and child negative expressivity at T1 were significantly correlated. Maternal negative expressivity at T1 significantly predicted child negative expressivity at T3. Children’s negative affectivity at T2 significantly predicted mothers’ negative expressivity at T3. Mothers’ positive expressivity was not related to children’s negative affectivity at any of the three time points. The findings demonstrate the reciprocal relations between children’s negative affectivity and maternal negative expressivity in the family, suggesting the importance of the interplay between child temperament and maternal expressivity within the family emotional context.